Can a Fast-Mode EUV Wave Generate a Stationary Front? - Chen P.F.; Fang C.; Chandra R.; Srivastava A.K. (My University, 2025)
The discovery of stationary “EIT waves” about 16 years ago posed a big challenge to the then favorite fast-mode wave model for coronal “EIT waves”. It encouraged various non-wave models and played an important role in convergence of the opposing viewpoints toward the recent consensus that there are two types of EUV waves. However, it was recently discovered that a stationary wave front can also be generated when a fast-mode wave passes through a magnetic quasi-separatrix layer (QSL). In this article, we perform a magnetohydrodynamic (MHD) numerical simulation of the interaction between a fast-mode wave and a magnetic QSL, and a stationary wave front is reproduced. The analysis of the numerical results indicates that near the plasma beta ∼1 layer in front of the magnetic QSL, part of the fast-mode wave is converted to a slow-mode MHD wave, which is then trapped inside the magnetic loops, forming a stationary wave front. Our results imply that we have to be cautious in identifying the nature of a wave, since there may be mode conversion during the propagation of the waves driven by solar eruptions. © 2016, Springer Science+Business Media Dordrecht.